2017
DOI: 10.3390/ijms18020429
|View full text |Cite
|
Sign up to set email alerts
|

Succinimide Formation from an NGR-Containing Cyclic Peptide: Computational Evidence for Catalytic Roles of Phosphate Buffer and the Arginine Side Chain

Abstract: The Asn-Gly-Arg (NGR) motif and its deamidation product isoAsp-Gly-Arg (isoDGR) have recently attracted considerable attention as tumor-targeting ligands. Because an NGR-containing peptide and the corresponding isoDGR-containing peptide target different receptors, the spontaneous NGR deamidation can be used in dual targeting strategies. It is well known that the Asn deamidation proceeds via a succinimide derivative. In the present study, we computationally investigated the mechanism of succinimide formation fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 86 publications
1
36
1
Order By: Relevance
“…Two H 2 O molecules and one dihydrogen phosphate (H 2 PO 4 − ) ion or one bicarbonate (HCO 3 − ) ion was included in the calculations as catalysts. These molecules and ions abundantly exist in vivo and have been suggested to catalyze post-translational modification of proteins [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. The optimized geometries of the cyclization step, which occur by nucleophilic attack by the ( N + 1) amide nitrogen to carbonyl carbon of the side chain, for the syn conformation in the phosphate-catalyzed reaction are shown in Figure 8 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two H 2 O molecules and one dihydrogen phosphate (H 2 PO 4 − ) ion or one bicarbonate (HCO 3 − ) ion was included in the calculations as catalysts. These molecules and ions abundantly exist in vivo and have been suggested to catalyze post-translational modification of proteins [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. The optimized geometries of the cyclization step, which occur by nucleophilic attack by the ( N + 1) amide nitrogen to carbonyl carbon of the side chain, for the syn conformation in the phosphate-catalyzed reaction are shown in Figure 8 .…”
Section: Resultsmentioning
confidence: 99%
“…Some computational studies have reported the succinimide formation mechanism of Asn and the changes of dihedral angles with the deamidation reaction using quantum chemical calculations [ 41 , 42 , 43 , 44 ]. The structural changes with succinimide formation from Asn are relatively small (change of N‒C α ‒C‒N and N‒C α ‒C β ‒C γ : 35–50°, C‒N‒C α ‒C: nearly constant) in comparison with other nonenzymatic modifications in some previous studies (the maximum change of dihedral angles: 214°) [ 45 , 46 , 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, arginine has been shown to facilitate Asu formation of an adjacent NG motif at near neutral and slightly acidic pHs by coordinating buffer anions that subsequently induce Asu cyclization via proton transfer. 52 Therefore, if arginine is contributing to the observed modification, it would be highly dependent on conformation and the chemistry of the local environment.…”
Section: Isomerization Events At Non-canonical Motifsmentioning
confidence: 99%
“…Next to daunorubicin, other drugs such as platinum IV, carboplatin and 5-fluorouracil were coupled to NGR peptides as well [43][44][45]. However, it is well known that the NGR motif can easily undergo Asn deamidation through succinimide formation followed by hydrolysis that can occur at both carbonyl groups of the cyclic imide leading to the formation of Asp and isoAsp residues with a usual ratio of 1:3 [46][47][48][49]. The speed of this process is highly influenced by numerous factors like peptide structure, temperature or pH of the solution.…”
Section: Introductionmentioning
confidence: 99%